'Defect-irrelevant' behavior of a no-insulation pancake coil wound with REBCO tapes containing multiple defects. (15th September 2016) - Hahn, Seungyong; Radcliff, Kyle; Kim, Kwanglok; Kim, Seokho; Hu, Xinbo; Kim, Kwangmin; Abraimov, Dmytro V; Jaroszynski, Jan
Abstract: A no-insulation (NI) pancake coil was wound with a 23 m long REBCO tape containing multiple 'defects', at which local critical currents are substantially lower (<80%) than the tape's lengthwise average. During a charging test up to 60 A in a bath of liquid nitrogen at 77 K, the test coil showed 'defect-irrelevant' behaviors, i.e. coil terminal voltages and center fields in steady-state operations were barely discernible from those of an ideal 'defect-free' coil. Also, the critical current ( I c ) of the coil was measured to be 68 A, close to 72 A estimated from the measured I c angular dependency data of a defect-free sample tape that was used for construction of the coil. The results demonstrate a potential to build a pancake coil with REBCO tapes regardless of their defects, which may lead to a substantial reduction in the construction cost of high field NI REBCO magnets.